Performative Semiotics of Manca' Paddang: Body, Sword, And Humor in the Construction of Selayar Cultural Meaning - Andi Taslim Saputra; Andi Fauziyah Hijrina Fatimah (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study analyzes manca' paddang, a traditional Selayar martial performance using swords, as a performative semiotic practice in which the body, object, and humor operate as cultural signs. Although the performance remains visible in ritual and community stages, it is often reduced to entertainment, thereby obscuring its role in transmitting values of courage, siri', social intimacy, and cultural memory. Using an interpretive qualitative design, data were collected over approximately three months in Galung Bontosikuyu, Benteng Bontoharu, Kayuadi, and Pulau Madu through passive observation, in-depth interviews, and visual documentation of performances. Charles Sanders Peirce's triadic model of representamen, object, and interpretant was used as the main analytical framework, complemented by performance studies perspectives on embodied action and cultural transmission. The findings show that the performer's body functions as a representamen through patterned movement, gesture, posture, and facial expression. The paddang or sword operates as an object that indexes courage, self-control, and disciplined masculinity while structuring dramatic interaction. Humor emerges as a dynamic interpretant through playful improvisation, laughter, and audience participation, transforming potential violence into social intimacy. The study argues that manca' paddang is not merely a traditional martial attraction but a complex cultural sign system in which Selayar identity is enacted, negotiated, and reproduced. It contributes to scholarship on Indonesian performance by integrating Peircean semiotics with performative analysis of embodied local knowledge.